THE ROLE OF PEACE BUILDING - Riak , Dr Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Peace building is an activity that aims to resolve injustice in nonviolent ways and to transform the cultural & structural conditions that generate deadly or destructive conflict. It revolves around developing constructive personal groups, and political relationships across ethnic, religious, class, national and racial boundaries. This process includes violence prevention, conflict managing, resolution, or transformation and post-conflict reconciliation or trauma healing, i.e., before, during, and after any given case of violence.